Physical assignment of the bovine MHC class IIa and class IIb genes - Hess, Markus M.; Goldammer, Tom; Gelhaus, A.; Ried, Karin; Rappold, Gudrun; Eggen, A.; Bishop, M. D.; Schwerin, M.; Horstmann, Rolf Dieter (Cytogenetics and cell genetics, 1999)
Screening of a bovine yeast artificial chromosome (YAC) library revealed two clones which contain most of the class II genes of the major histocompatibility complex (MHC) known to date. The YACs were mapped by fluorescence in situ hybridization (FISH) and characterized for the class II genes they contain. We found that the classic class II genes BoLA- DQA, -DQB, -DRA, and -DRB3 are located at BTA 23q21 and the non-classic class II genes DYA, DIB, LMP2, LMP7, TAP2, BoLA-DOB, -DMA, -DMB, and -DNA are located at BTA 23q12→q13. These two different mapping locations confirm and extend previous findings of a gross physical distance between classic and non-classic MHC class II genes in cattle.
Gesehen am 06.04.2021